Die plasmaferese eenheid van die Johannesburg-Hospitaal - C.M. Janse van Rensburg (AOSIS, 1983)
The plasmapheresis unit at the Johannesburg Hospital is part of the haematology day clinic. It is visited by patients suffering from conditions which can be treated by plasma exchange. Nurses working in this unit are specially trained regarding the techniques used, orientation of patients and possible complications of the procedure.